Admission Policies in Loss Queueing Models with Heterogeneous Arrivals - Carrizosa, E.; Conde, E.; Muñoz-Márquez, M. (Management Science, 1998)
In this paper we consider a loss system where the arrivals can be classified into different groups according to their arrival rate and expected service time. While the standard admission policy consists of rejecting only those customers who arrive when all servers are busy, we address the problem of finding the optimal static admission policy (with respect to a given reward structure) when customers can be discriminated according to the group they belong to, thus customers of some groups might be automatically rejected (even if some servers remain idle) in order to enhance the global efficiency of the system. The optimality of a cμ-rule is shown, from which finite-time algorithms for the one- and two-server cases are derived.